2016
DOI: 10.1186/s12985-016-0495-5
|View full text |Cite
|
Sign up to set email alerts
|

Evasion of host antiviral innate immunity by HSV-1, an update

Abstract: Herpes simplex virus type 1 (HSV-1) infection triggers a rapid induction of host innate immune responses. The type I interferon (IFN) signal pathway is a central aspect of host defense which induces a wide range of antiviral proteins to control infection of incoming pathogens. In some cases, viral invasion also induces DNA damage response, autophagy, endoplasmic reticulum stress, cytoplasmic stress granules and other innate immune responses, which in turn affect viral infection. However, HSV-1 has evolved mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
124
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(126 citation statements)
references
References 109 publications
(109 reference statements)
2
124
0
Order By: Relevance
“…Therefore, HSV-1 also evolved strategies to evade NF-B signaling during infection and to balance the promoting and suppressing effects for its propagation. Studies have reported that HSV-1 uses a variety of proteins, mostly tegument proteins, to maintain effective infection (34). ICP0, an E3 ubiquitin ligase, disrupts NF-B activation by abrogating p65 nuclear translocation and promoting p50 to proteasomal degradation (35).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, HSV-1 also evolved strategies to evade NF-B signaling during infection and to balance the promoting and suppressing effects for its propagation. Studies have reported that HSV-1 uses a variety of proteins, mostly tegument proteins, to maintain effective infection (34). ICP0, an E3 ubiquitin ligase, disrupts NF-B activation by abrogating p65 nuclear translocation and promoting p50 to proteasomal degradation (35).…”
Section: Discussionmentioning
confidence: 99%
“…During this process, HSV can activate multiple signal transduction pathways, including Nuclear Factor kappa B (NF-κB), interferon (IFN) Regulatory Factors (IRFs) and Mitogen-Activated Protein Kinase (MAPK) pathways, resulting in induction of cytokine production in HSV-infected cells [14,15]. Stimulation of NF-κB and IRF pathways occur when HSV glycoprotein H/L complex interacts with the αvβ 3-integrin signaling pathway, which results in induction of type I IFNs [16].…”
Section: Host Responses Against Hsv Infectionmentioning
confidence: 99%
“…As a master of immune evasion, HSV-1 has evolved multiple strategies to counteract host antiviral responses (14). Although much progress has been made in understanding the mechanisms of HSV-1-mediated immune evasion, most of these findings focused on Toll-like receptor-and RLR-mediated signaling pathways, and our understanding of how HSV-1 evades cellular DNA sensing pathways is still quite limited.…”
mentioning
confidence: 99%